A multi-model simulation framework for the 'Sponge Park' concept: achieving urban water-energy nexus sustainability in hyper-arid climates - Firas Fayssal (BIORE Scientia Academy, 2026)
Urban areas in hyper-arid regions face a dual threat of water scarcity and urban heat islands, exacerbated by conventional infrastructure. This study introduces and evaluates the